Circ_0001273 downregulation inhibits the growth, migration and glutamine metabolism of esophageal cancer cells via targeting the miR‐622/SLC1A5 signaling axis. Issue 12 (13th May 2022) - Wu, Bomeng; Chen, Ying; Chen, Ying; Xie, Xihao; Liang, Hanping; Peng, Fengyuan; Che, Weibi
Abstract: Background: Esophageal cancer is a relatively rare cancer. However, its death rate is not to be taken lightly. Accumulating evidence indicates circular RNA (circRNA) is implicated in cancer development. The objective of this study was to unveil the role of circ_0001273 in esophageal cancer (EC). Methods: For expression analysis of circ_0001273, miR‐622 and solute carrier family 1 member 5 (SLC1A5), quantitative real‐time PCR (qPCR) and Western blot were conducted. Cell proliferation was evaluated by cell counting kit‐8 (CCK‐8), EdU and colony formation assays. Cell apoptosis and cell migration were investigated using flow cytometry assay and wound healing assay. Glutamine metabolism was assessed by glutamine consumption and glutamate production using matched kits. The predicted binding relationship between miR‐622 and circ_0001273 or SLC1A5 was validated by dual‐luciferase reporter assay. An in vivo xenograft model was established to determine the role of circ_0001273 on tumor growth. Results: Circ_0001273 was upregulated in EC tumor tissues and cells. Knockdown of circ_0001273 repressed EC cell proliferation, migration, epithelial‐mesenchymal transition (EMT) and glutamine metabolism. Circ_0001273 knockdown also blocked tumor development in animal models. MiR‐622 was targeted by circ_0001273, and its inhibition reversed the functional effects of circ_0001273 knockdown. SLC1A5 was a target gene of miR‐622, and circ_0001273 targeted miR‐622 to positively regulate SLC1A5 expression. The inhibitory effects of miR‐622 enrichment on EC cell proliferation, migration, EMT and glutamine metabolism were recovered by SLC1A5 overexpression. Conclusion: Circ_0001273 high expression contributed to EC progression via modulating the miR‐622/SLC1A5 signaling axis. Abstract : Circ_0001273 was highly expressed in esophageal cancer. Circ_0001273 functionally promoted esophageal cancer cell proliferation, migration and glutamine metabolism, attenuated cell apoptosis and enhanced tumor growth in vivo. Mechanistic analysis revealed that circ_0001273 acted as an miR‐622 sponge to increase the expression of oncogenic SLC1A5.